P220 Role Of Ebus-tbna In The Diagnosis Of Primary And Relapsing Haematological Malignancy. (10th November 2014) - Thakrar, RM; Hardavella, G; Brown, JM; Succony, L; Falzon, M; Borg, E; Jeebun, V; Munnavar, M; Janes, SM; Navani, N
Abstract : Introduction: Endobronchial ultrasound and transbronchial needle aspiration (EBUS-TBNA) has been embraced as a breakthrough in the diagnosis and mediastinal staging of lung cancer. However, its utility in determining a diagnosis of lymphoma is not well defined, and is currently not recommended by the British Thoracic Society. Aim: Evaluate the role of EBUS-TBNA in the diagnosis and subtyping of haematological malignancies. Method: Patients referred with mediastinal lymphadenopathy for EBUS-TBNA in whom lymphoma was suspected, were identified retrospectively in 3 tertiary centres in the UK between 2008 and 2013. EBUS was performed using a linear array ultrasonic bronchoscope and specimens taken with a 21 or 22 gauge needle. The diagnostic accuracy, avoidance of mediastinoscopy and surgical biopsy in cases of primary and relapsing haematological malignancy was recorded. Where EBUS-TBNA was negative, patients subsequently underwent surgical biopsy or clinical and radiological surveillance. Results: Twenty-four patients (10 female and 14 male) with a mean age of 55.5 years underwent EBUS-TBNA for evaluation of mediastinal lymphadenopathy. Clinical and radiological diagnosis was of either, isolated mediastinal lymphadenopathy of unknown cause (n = 15) or suspected mediastinal recurrence of lymphoma (n = 8). Five patients (62.5%) were found to have a relapse of their haematological malignancy, whilst a new diagnosis of lymphoma was made in 11 cases (73.3%) where the presentation was of isolated mediastinal lymphadenopathy. One patient in this group was found to have tuberculosis. Tissue obtained from nodal aspiration was sufficient to subtype the disease in detail in 14 patients with immunohistochemistry. Overall, 17 patients (70%) were prevented from having mediastinoscopy and other biopsies, and the diagnostic accuracy and sensitivity of EBUS-TBNA in primary and relapsing lymphoma was 74%. Conclusion: EBUS-TBNA is a safe and important approach to mediastinal lymphadenopathy in suspected lymphoma, whereby detection of either primary or relapsing haematological malignancy prevents need for other more invasive biopsies.